HIL in a Vehicle Washing Process Implementing MQTT Communication Network based in TCP/IP - Torres, Bryan (2024)
This work describes the documentary synthesis of the design and adaptation of an industrial environment of an automatic car washing machine with tunnel type structure. The same one that has four stations properly distributed, with respect to the time and operation of the mechanisms of the washer with the objective of improving the operation of the system and saving water. This automated industrial process is virtualized in the graphic development platform Unity for its adaptation to a Hardware in the Loop (HIL) control loop. The whole process is carried out by means of a programming logic unit (PLC); considering an automatic control of the stations carried out in LOGOSOFT software. The communication of the network is made by means of an Ethernet architecture based on TCP-IP, in addition the use of the MQTT communication protocol is presented based on its fluidity, simplicity and lightness that makes it suitable for its use in programmable controllers, the communication network is designed in Node-Network.